Evaluation of Mammals Hunting in Indigenous and Rural Localities in Eastern Brazilian Amazon - Mesquita, Geison Pires; Barreto, Larissa Nascimento (Ethnobiology and Conservation, 2015)
Hunting is responsible for the decline of more than half of all mammal species from Brazil; however, very few studies relating to hunting exist for the Eastern region of the Amazon. Medium- and large-sized mammals are valued for their protein and are thus more affected by hunting activity. Published studies on hunting in the region were quantitatively analyzed and used to determine the biomass and extraction rates of species and groups of species, considering the characteristics of each group, as well as the differences and similarities in composition in each type of game in the locality. A total of 32 species from eight orders and 17 families were hunted, totaling 32,726,990 kilograms of game meat. A positive correlation was found between biomass, the number of animals slaughtered and the number of species. Ungulates were the most hunted group, from which the most biomass was obtained. Concerning food preferences, frugivores represented the highest number of species hunted and also the highest biomass, and a positive correlation existed between the extraction rate and ungulate biomass. There was no significant difference between the diversity of mammals of different indigenous and rural localities; however, from a multidimensional analysis of the localities, A’Ukre and Alto Turiaçu were more similar to each other, and were more distant from the other groups. Knowledge concerning which species and groups and how many animals are hunted in each locality is necessary to direct conservation management plans and increase their efficiency within localities.